Distinct pathological changes of osteochondral units in early OVX-OA involving TGF-β signaling - Yang, Zihuan; Tan, Qizhao; Zhao, Zhenda; Niu, Guodong; Li, Siwei; Li, Weishi; Song, Chunli; Leng, Huijie (Frontiers in Endocrinology, 2022)
Different opinions exist about the role of subchondral bone in osteoarthritis (OA), probably because subchondral bone has different effects on cartilage degeneration in OA induced by different pathologies. Considering the effects of estrogen on bone metabolism, the physiological changes and pathogenesis of the osteochondral unit in ovariectomy-induced OA (OVX-OA) might be distinct from other types of OA. The osteochondral alterations of post-traumatic OA (PT-OA) and OVX-OA at week 9 after surgery were compared. Then the alterations of osteochondral units in OVX-OA rats were tracked over time for the designed groups: Sham, OVX and OVX rats treated with estrogen (OVX+E). DXA, micro-CT, and histochemical staining were performed to observe alterations in osteochondral units. Rapid cartilage degeneration and increased bone formation were observed in PT-OA, while only mild cartilage erosion and significant bone loss were observed in OVX-OA at week 9 after surgery. Subchondral bone degradation preceded cartilage degeneration by 6 weeks in OVX-OA. TGF-β expression was downregulated in the osteochondral unit of OVX rats. Estrogen supplementation inhibited subchondral bone loss, cartilage degradation and TGF-β expression decrease. Subchondral bone may play critical and distinct roles in early OVX-OA. Both estrogen supplementation and TGF-β modulation at the early stage of OVX-OA could be effective treatments for post-menopausal OA.